THE PRACTICE OF PUBLIC FLOGGING IN THE PERSPECTIVE OF INTERNATIONAL HUMAN RIGHTS IN NANGGROE ACEH DARUSSALAM INDONESIA - Edward M.L. Panjaitan; Hillary Tjandra (Pusat Strategi Kebijakan Hukum dan Peradilan Mahkamah Agung RI, 2022)
Indonesia is a unitary state on which national law applies in all the provinces. The national law applied throughout Indonesia regulates civil, criminal, commercial, and other aspects of Indonesian society. However, an exception to the national law application exists in the Province of Nanggroe Aceh Darussalam, especially in the type of sanctions applicable towards the convicts who have committed or violated criminal law in Nanggroe Aceh Darussalam. Nanggroe Aceh Darussalam implements a different criminal law from the national criminal law applicable to other regions in Indonesia. This is due to the issuance of Law No. 11 of 2006 on Aceh Government, which gave the Aceh Province special authority to adopt and practice Islamic law to its people. One form of punishment applied in Nanggroe Aceh Darussalam is the practice of flogging carried out in public (public flogging). This form of sanction has attracted the attention of the UN Special Rapporteur who recommended that the sentence be abolished, due to its practice which is contrary to international conventions that have been ratified by Indonesia. This article will discuss the legalization of public flogging practice in Indonesia following the international conventions on which Indonesia is its member.